Penerapan Permainan Ular Tangga pada Operasi Bilangan Bulat Siswa Sekolah Dasar - Ari Indriani; Junarti Junarti; Ula Lu’luatul Hidayah (IKIP PGRI Bojonegoro, 2020)
Abstract: Learning system at SD Negeri 3 Kunduran still uses conventional learning and teachers do not use teaching aids. This is a factor causing low student achievement. The purpose of this study was to determine the application of the snake and ladder game on integer operations (addition and subtraction) of elementary school students. This research uses qualitative descriptive approach. The research subjects were grade II students totaling 26 students. The data collection techniques used were the observation method, description test, and documentation. The data analysis technique used is the qualitative data analysis model of Miles and Hubermen, including data reduction, data presentation and conclusion drawing. The result of this research are: learning mathematics by applying the snake and ladder games makes it easy for students to understand mathematical concepts and makes it easy for teachers to explain addition and subtraction material. The conclusion of this research is that mathematics learning by using snakes and ladders gams can be applied to integer operating materials, especially the addition and subtraction of grade II elementary school students. Students who scored above the KKM there were 23 students (88.46%).Keywords: snakes and ladder Games Abstrak: Sistem pembelajaran di SD Negeri 3 Kunduran masih menggunakan pembelajaran konvensional dan guru kurang menggunakan alat peraga. Hal ini merupakan faktor penyebab prestasi belajar siswa rendah. Tujuan penelitian ini untuk mengetahui penerapan permainan ular tangga pada operasi bilangan bulat (penjumlahan dan pengurangan) siswa sekolah dasar. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Subyek penelitian adalah siswa kelas II yang berjumlah 26 siswa.Teknik pengumpulan data yang digunakan yaitu metode observasi, tes uraian, dan dokumentasi. Teknik analisis data yang digunakan adalah analisis data kualitatif model Miles dan Hubermen, meliputi reduksi data, penyajian data dan penarikan kesimpulan. Hasil dari penelitian ini adalah pembelajaran matematika dengan menerapkan alat peraga ular tangga memudahkan siswa memahami konsep matematika dan memudahkan guru dalam menjelaskan materi penjumlahan dan pengurangan. Kesimpulan penelitian ini adalah pembelajaran matematika dengan menggunakan permainan ular tangga dapat diterapkan pada materi operasi bilangan bulat khususnya penjumlahan dan pengurangan siswa kelas II SD. Siswa yang memperoleh nilai di atas KKM ada 23 siswa (88,46%). Kata Kunci: Permainan Ular Tangga